O juiz de garantias como vetor de maximização do direito fundamental à jurisdição penal imparcial: reflexões à luz da epistemologia e da psicologia cognitiva - Melo, Gabriellen Carneiro de (2023)
The main objective of the research is to investigate, through a transdisciplinary study between epistemology, between cognitive psychology and behavioral psychology, the existence of conditions for the exercise of impartiality in Brazilian Procedural Law and the (in)dispensability of the implementation of the figure of the guarantees judge brought by Law nº 13.964/2019 to achieve the aforementioned objective, in order to achieve a Criminal Procedure in accordance with the Constitution. For this, we seek to examine in which type of criminal procedural system impartiality is sacrificed (accusatory or inquisitorial), also analyzing which system is proposed by the Federal Constitution and how the Code of Criminal Procedure contradicts it. Next, we intend to investigate the problems arising from the epistemological emptiness of the discourse of real truth, inherent to the inquisitorial system, exploring the obstacles caused by the cognitive limitations of the human being. In addition, it investigates how the "truth" is inserted in the process through the evidence, with a focus on the management of evidence by the judge, inquiring the consequences of the judge's instructional powers for a Criminal Procedure in accordance with the Constitution and the legal and psychic effects for the result of the process. It also researches the involuntary cognitive processes that occur in the human subconscious at the time of criminal judicial decision-making, which can subject the judge to numerous heuristics and biases that have the power to influence the outcome of the lawsuit. In addition, the cognitive dissonance experienced by the judge after making a decision or a first impression is examined, investigating the repercussions of this on his impartiality. Finally, we seek to determine the new system brought about with the implementation of the guarantee judge, comparing it with some models present in external legal systems, as well as facing the grounds presented by the Federal Supreme Court that cautiously suspended its validity since 2020, therefore, answer if there are legal and scientific foundations to support the implementation of the guarantees judge in Brazil. It is concluded that impartiality can only be exercised in an accusatory-type system, with the guarantees judge functioning as a vector for maximizing the fundamental right to impartial criminal jurisdiction.